AKAD IJARAH MUNTAHIYAH BITTAMLIK PERBANKAN SYARIAH SEBAGAI SEWA MANFAAT: AKAD IJARAH MUNTAHIYAH BITTAMLIK PERBANKAN SYARIAH SEBAGAI SEWA MANFAAT - Deva Nabilah; Shofwatul Alaqoh; Benny Sultan (KASBANA, 2024)
Ijarah Muntahiyah Bittamlik is a combination of two rental agreements between the bank as the lessor and the customer as the lessee for an item which is the object of the rental for a certain period of time through payment of rent by the customer to the bank, which binds the bank to transfer ownership of the rental object to the lessee after end of rental period. This research examines the perspective or views of Sharia Economic Law on ijarah Muntahiyah bittamlik as a lease of benefits for sharia banking practices. The type of research data is normative juridical using data collection methods in the form of library studies by collecting documents and data to be processed using analytical methods. The results of this research are that Sharia Banks apply ijarah mutaniah bi at-tamlik as a product in medium-term and long-term financing intended for; a) Investment Financing where banks channel financing for the procurement of productive capital goods such as machines, b) Consumer Financing such as purchasing houses, cars etc. Keywords: Ijarah Muntahiyah Bittamlik, Sharia Banking, Benefit Leasing.